Metal and metal oxide nanoparticle synthesis from metal organic frameworks (MOFs): finding the border of metal and metal oxides - Das, Raja; Pachfule, Pradip; Banerjee, Rahul; Poddar, Pankaj (Nanoscale, 2012)
Herein, for the first time, we report a generalized strategy for the successful synthesis of highly crystalline metal and metal oxide nanoparticles embedded in a carbon matrix by the controlled thermolysis of metal organic frameworks (MOFs). The rationalized synthesis strategy of a broad range of metal and metal oxides nanoparticles, such as Cu/CuO, Co/Co3O4, ZnO, Mn2O3, MgO and CdS/CdO, by thermolysis of MOFs demonstrates for the first time that metal ions with a reduction potential of -0.27 volts or higher present in MOFs always form pure metal nanoparticles during thermolysis in N-2, whereas metal ions with a reduction potential lower than -0.27 volts form metal oxide nanoparticles during thermolysis in N-2. Another point of interest is the fact that we have found a unique relationship between the nanoparticle size and the distance between the secondary building units inside the MOF precursors. Interestingly, the crystallinity of the carbon matrix was also found to be greatly influenced by the environment (N-2 and air) during thermolysis. Moreover, these nanoparticles dispersed in a carbon matrix showed promising H-2 and CO2 adsorption properties depending on the environment used for the thermolysis of MOFs.

Metal [Zn(II), Cd(II)], 1,10-phenanthroline containing coordination polymers constructed on the skeleton of polycarboxylates: synthesis, characterization, microstructural, and CO2 gas adsorption studies - Yadav, Pramod Kumar; Kumari, Niraj; Pachfule, Pradip; Banerjee, Rahul; Mishra, Lallan (Crystal Growth & Design, 2012)
{Four new coordination polymers have been obtained by the reaction of metal [Zn(II), Cd(II)], 1,10-phenanthroline separately with two carboxylic acids, [biphenyl-4,4'-dicarboxylic acid (4,4'-H(2)BDA),and 4,4'-azodibenzoic acid (4,4'-H(2)ADA)]. The crystal structures of the resulting complexes of type {[Zn(4,4'-BDA)(Phen)(2)center dot HCON(CH3)(2)}(n) (1), {[Cd(4,4'-BDA)(Phen)](2)center dot H2O\

Multifunctional and robust covalent organic framework-nanoparticle hybrids - Pachfule, Pradip; Panda, Manas K.; Kandambeth, Sharath; Shivaprasad, S. M.; Diaz, David Diaz; Banerjee, Rahul (Journal of Materials Chemistry A, 2014)
Highly dispersed Pd(0) nanoparticles were successfully immobilized into a stable, crystalline and porous covalent organic framework (COF), TpPa-1, by a solution infiltration method using NABH(4) as a reducing agent. High resolution and dark field TEM images confirmed the uniform loading of the Pd(0) nanoparticles into the TpPa-1 matrix without aggregation. This hybrid material exhibited excellent catalytic activity towards the Cu free Sonogashira, Heck and sequential one pot Heck-Sonogashira cross-coupling reactions under basic conditions, and with superior performance compared to commercially available Pd supported on activated charcoal (i.e., 1, 5 and 10 wt%). Additionally, the precursor Pd(II)-doped COF also displayed competitive catalytic activity for the intramolecular oxidative biaryl synthesis under acidic conditions. Both catalysts were found to be highly stable under the reaction conditions showing negligible metal leaching, non-sintering behavior, and good recyclability. To the best of our knowledge, the organic support used in this work, TpPa-1, constitutes the first COF matrix that can hold both Pd(0) nanoparticles and Pd(II) complex without aggregation for catalytic purposes under both highly acidic and basic conditions.